A form of multivariate generalised exponential family of distribution. Issue 5 (3rd September 2017) - David Sam Jayakumar, G. S.; Solairaju, A.; Sulthan, A.
Abstract: David Sam et.al(2012) proposed a Generalised Multivariate additive exponential distribution and further David Sam et.al(2014) extend the work by proposing Multivariate Generalized double exponential family of distribution of kind-1. In this paper, the authors bring out a family of exponential distributions in a generalized multivariate form which leads to explore more than 25 special cases of generalized multivariate exponential distribution. In subsequent sections, authors proposed distribution and its special cases are discussed.